The Role of Experiential Marketing Towards Purchase Intention in Vertical Building Property Mediated by Brand Image and Brand Awareness - Raditya, Andreas; Harianto, Eric; Nahar, Faiza Husnayeni (Jurnal Aplikasi Manajemen, 2024)
The Covid-19 pandemic has caused various behavioral changes in society, especially in business. People's consumption behavior has shifted to the consumption of daily necessities products, so that sales in property have decreased. This study aims to examine the effect of Experiential Marketing on Purchase Intention at the Ciputra International Jakarta Superblock Project. This research uses a quantitative design using SEM-PLS analysis. The population in this study is sales candy data obtained through Instagram booster ads in the Jakarta area of as many as 334 people, which is also determined by the number of saturated samples. The results showed that experiential marketing variables have a significant influence on brand image and brand awareness. Brand image and brand awareness variables have a significant and positive effect on Purchase Intention. In addition, the results of the mediation of Experiential Marketing variables mediated by Brand Image and Brand Awareness variables have a positive and significant effect on Purchase Intention. The implication of this research is that experiential marketing activities (sense, feel, think, act, and relate) are needed to improve brand image and brand awareness so that they can help increase consumer purchase intention in the vertical building property industry.